Strategi Pengembangan Desa Beruk Sebagai Desa Wisata - Putri Permatasari; Joko Winarno; Sapja Anantanyu; Agung Wibowo; Suwarto Suwarto; Suryono Suryono (STKIP Andi Matappa, 2021)
Community service activities are carried out in partnership with the government of Beruk Village, Jatiyoso District, Karanganyar Regency. This activity aims to increase public awareness and participation in the development of Beruk village so that it can become an agriculture-based tourism village. The implementation method is carried out through socialization, workshops and group discussion forums (FGD). The results of community service activities are an increase in the cognitive aspects of members of the Beruk village community related to the natural potential that can be managed into a tourist village so that it can improve the residents’ economny, cognitive enhancement of farmers in running farming on conservation land so that they can support agriculture-based tourism village programs and cognitive enhancement village government officials in managing Bumdes so as to provide information on the formation, management and efforts to establish Beruk village as a tourist village